Pengaruh Work-Life Balance, Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan PT Buana Samudra Lestari - Sefna Efrideyesa use; Pemilia Sulistyowati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The purpose of this study is to determine and examine the impact of Work-Life Balance on the performance of PT Buana Samudra Lestari employees, the impact of the work environment on the performance of PT Buana Samudra Lestari employees, the impact of compensation on the performance of PT Buana Samudra Lestari employees, and the simultaneous impact of Work-Life Balance, work environment, and compensation on the performance of PT Buana Samudra Lestari employees. The sample of this quantitative study was ninety respondents. Multiple linear regression analysis was conducted using IBM SPSS Statistics. The findings of this study indicate that Work-Life Balance affects the performance of PT Buana Samudra Lestari store employees, that the work environment significantly affects the performance of PT Buana Samudra Lestari store employees, that compensation significantly affects the performance of PT Buana Samudra Lestari store employees, and that Work-Life Balance, work environment, and compensation all have an impact on the performance of PT Buana Samudra Lestari store employees at the same time.